Branch Grading as a Framework to Improve Business Growth and Bank Branch Performance - Jacoub, Yutrizal; Syabarrudin, Agus (Research of Accounting and Governance, 2025)
This study examines the impact of implementing a branch grading system on business performance across 46 branches of Bank "X" over a four-month period (August–October 2024). Using a descriptive quantitative approach, the study analyzes monthly performance data, including funding, lending, profit before tax (NPBT), number of accounts, transaction volume, and local market potential. The findings show that 14 branches (30.4%) improved their grade by September 2024, just two months after implementation. The grading system effectively aligns internal performance with external market potential, enhancing managerial accountability, optimizing resource use, and improving customer satisfaction. It provides a strategic, data-driven tool for performance monitoring and targeted growth. The results suggest that grading can guide resource allocation, performance-based incentives, and policy development, especially for branches with high market potential but low output. This study offers empirical evidence supporting the use of integrated internal-external metrics in branch management. It also contributes to the limited research on data-driven performance evaluation in Indonesian banking and highlights the model’s relevance amid digital transformation and branch rationalization efforts. The proposed grading system is practical, replicable, and valuable for strategic decision-making in branch optimization.